Індивідуальний дискурс «еміграційної» прози Т. Бордуляка у світлі сучасних літературознавчих методологій - Осьмак, Ніна; Osmak, Nina (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розкрито особливості індивідуального дискурсу «еміграційної» прози Т. Бордуляка. Зроблено висновок про особливий тип взаємодії «автор – герой», що характеризує ставлення письменника до актуальної проблеми впливу еміграції на формування особистісного «я» героя, його усвідомлення власного призначення, можливості до самореалізації тощо. The article reveals the peculiarities of individual discourse emigration prose by T. Borduliak. Of course, the topic of emigration peasants doomed to death by starvation in his native province was close to the writer. It is no coincidence he was the first who implemented it in works of art. The stories have a fresh flavor and real people with their bleak thoughts, attempt a psychological analysis, which Panas Myrny began and V. Stefanyk brought to the filigree techniques. Careful attention to human psychology, his spiritual «І» is the evidence of searches by T. Borduliak towards the enrichment of artistic means in the reflection of the multifaceted and complex, sometimes too contradictory human personality. During the analysis we concluded a special type of interaction «author – hero», which characterizes the attitude of the writer to the actual problem of the effect of emigration on the formation of the personal «І» character, his awareness of his own destiny, opportunities for self-fulfilment and the like.
Individual Discourse of Emigration Prose by T. Borduliak in Accordance with the Methodology of Modern Literary
Keywords: оповідання; конфлікт; еміграція; художній образ; фольклор; символіка; story; conflict; emigration; artistic image; folklore; symbols